Quantum anonymous one-vote veto protocol based on BB84 states - Runhua SHI; Hui YU; Weiyang KE; Xiaotong XU (Tongxin xuebao)
In order to construct unconditionally secure one-vote veto protocol, a primitive protocol of secure multiparty computations was defined, i.e., secure multiparty disjunction.Furthermore, by introducing a quantum cloud, a quantum secure multiparty disjunction (QSMD) protocol was proposed.BB84 states were took as quantum resources and only single-photon operations and measurements were needed.To avoid the flaws of infeasibility, i.e., most of existing quantum voting protocols need to perform operations and measurements in high-dimensional Hilbert space, a quantum anonymous one-vote veto protocol with a quantum cloud (QAOVC) was designed by using the QSMD protocol.In addition, to decentralize, a quantum anonymous one-vote veto (QAOV) protocol without any third party was presented.Compared with related protocols, the proposed protocols require less quantum resources and simpler operations, so they have better feasibility.Under the semi-honest model, quantum perfect encryption and classical one-time pad can ensure the unconditional security of the proposed protocols, i.e., it can completely meet secure requirements of one-vote veto and perfectly protect the privacy of the voters.Finally, simulation experiments are implemented on IBM Qiskit, and the experimental results show that the protocols are correct and feasible.